Turkish Migrant Women with Recurrent Depression: Results from Community-based Self-help Groups. Issue 2 (3rd April 2017) - Siller, Heidi; Renner, Walter; Juen, Barbara
ABSTRACT: The study focuses on psychosocial functioning of female Turkish immigrants in Austria with recurrent depressive disorder participating in self-help groups. Self-help groups guided by group leaders of Turkish descent should increase autonomy in participants, providing the opportunity to follow their ethnic health beliefs. Turkish immigrant women ( n = 43) with recurrent depressive disorder participated in self-help groups over four months. Qualitative data of participants and group leaders, containing interviews, group protocols and supervision protocols of group leaders were analyzed using the qualitative content analysis for effects on psychosocial function, such as interaction with others, illness beliefs and benefit from self-help group. Women reported feelings of being neglected and violated by their husbands. They stated that they had gained strength and had emancipated themselves from their husbands. Self-help groups functioned as social resources and support for changes in participants' lives. Further interventions should integrate the functional value of depressive symptoms and focus on social support systems and social networks.